Mechanisms and technologies for fostering the research and innovative capability in university teachers - Olga Tapalova; Nadezhda Zhiyenbayeva; Ulzharkyn Abdigapbarova (OmniaScience, 2024)
This study aims to examine the effects of the "Unlocking Research & Innovative Capability" program for university teachers. A total of 80 teachers from the [BLINDED] University were enrolled. All participants were divided into groups based on their age and teaching experience. Data were collected via surveys. The proposed program was found to have different effects across groups. Young university teachers (28 to 35 years; teaching experience, 3 to 5 years) exhibited improvement in all research and innovative capability variables, ranging from 0.84 in Interdisciplinary Cooperation to 2.63 in Innovative Teaching. The same is true for early middle-aged university teachers (36 to 45 years; teaching experience, 5 to 10 years) who showed improvement ranging from 1.52 in Interdisciplinary Cooperation to 3.00 in Integration of Technology. Older middle-aged university teachers (46 to 55 years; teaching experience, 10 to 20 years) exhibited improvement in their Innovative Teaching, Research Practice, and Integration of Technology; yet, it did not exceed 1.85 points. Older university teachers (older than 56 years; teaching experience, 20 years) demonstrated minimal improvement in all dimensions. This study was conducted as part of governmental research on "Managing the Development of Research & Innovative Capability in the Research University Staff under the Participatory Management Model" launched by the RK Ministry of Education and Science (Project number: AR14872123). The study emphasizes the importance of empowering university teachers as key drivers of research, knowledge generation, and innovative teaching. The present findings can be used to cultivate a culture of innovation and research in academic institutions.